Cult Places and Cultural Change in Republican Italy A Contextual Approach to Religious Aspects of Rural Society after the Roman Conquest - Stek, Tesse (Amsterdam Archaeological Studies, 2009)
This scholarly study throws a new light on the Roman impact on religious structures in Republican Italy. In the last four centuries BC, Italy went through immense changes. The Apennine and Adriatic areas were originally inhabited by various 'Italic' tribes and characterised by a specific non-urban societal organisation, in which cult places had a pivotal function. From the fourth century BC onwards the area was gradually incorporated by Rome, profoundly altering its geopolitical make-up. The author not only investigates the changing social and political function of cult places in non-Roman Italic society, he also highlights the importance of cult places and religious rituals for new Roman communities in the conquered areas. This research thus opens new perspectives on the issue of the 'religious romanisation' of Italy by arguing for a strong Roman impact also in non-urbanised areas. Tesse Stek bases his study on the analysis of archaeological, literary and epigraphic evidence from rural cult places in Central and Southern Italy, including field work on the Samnite temple of S. Giovanni in Galdo. Amsterdam Archaeological Studies is a series devoted to the study of past human societies from the prehistory up into modern times, primarily based on the study of archaeological remains. The series will include excavation reports of modern fieldwork; studies of categories of material culture; and synthesising studies with broader images of past societies, thereby contributing to the theoretical and methodological debates in archaeology. This title is available in the OAPEN Library - http://www.oapen.org.